Does socio-demographic variables matter in explaining issues and challenges in Islamic microfinance? Evidence from Malaysia - Che Mohd Salleh, Marhanum; Kassim, Salina; Kassim, Siti Nadhirah (KnE Publishing, 2019)
Purpose - In line with the wide acceptance of the microfinance industry globally, Islamic microfinance has also evolved rapidly in the past years to cater for the demand for Shariah-compliant microfinancing schemes. Despite this, the industry is facing various issues and challenges from both the clients and microfinance institutions. This study aims to identify the issues and challenges faced by different demographic background of microentrepreneurs receiving Islamic microfinancing from Amanah Ikhtiar Malaysia (AIM). Methodology- It adopts the quantitative research methodology where primary data is collected using survey questionnaires administered on 393 women entrepreneurs who are currently clients of AIM’s Islamic microfinance scheme located in Selangor. The descriptive and cross-tabulation analyses are applied in efforts to understand the influence of socio-demographic factors (age, education level, duration with AIM, and times of receiving financing) on the following issues: cost of repayment, financing period, amount of financing, distance to AIM center, group lending mechanism, discipline among members, problematic group members, and consultation services. Findings - The study finds that clients with different socio-demographic factors perceived the issues differently, suggesting an influential role of clients’ demographic factors on the microfinance intervention. Practical implications - These findings have important implications to the microfinance industry in terms of further improving their products that are tailor-made to the socio-demographic characteristics of their clients. Originality – This research taken views of AIM’s microfinance recipients which were woman entrepreneurs in Selangor directly through a survey. Results of the research would be useful to AIM to enhance their products and services in future.